Menjaga Kekudusan Hidup: Refleksi Anak-Anak Allah Berdasarkan Galatia 3:26 - Gabriel A.P. Saragih; Fernando A.M. Saragih (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This article explores the importance of maintaining holiness of life as a response to God's work of salvation through Jesus Christ, based on Galatians 3:26. Holiness of life reflects the identity of God's children and is a calling for every believer to live according to His will. Modern challenges such as the influence of social media, materialistic lifestyles, and promiscuity often hinder holy living. However, through the guidance of the Holy Spirit and spiritual disciplines, believers can stick to Biblical values and maintain their holiness. This article uses a qualitative approach with text analysis to explore the theme of holiness of life and its relevance for Christians today. The results are expected to help readers understand the importance of maintaining holiness as part of their identity as children of God.